The clinical and laboratory profile of dengue fever in a tertiary care hospital - Sujitha, Katari; Dorasanamm, M.; Nagabhushana, M. V. (International Journal of Advances in Medicine, 2019)
Background: Dengue fever is one of the most common acute viral illness associated with considerable morbidity and mortality. Recently, there is an alarming rise of dengue in India. This study was undertaken to know the clinical profile and laboratory findings during the evolution of dengue fever. Methods: A total of 120 patients of dengue fever who were NS1 antigen or IgM dengue positive, admitted to medical wards of Narayana Medical College, Nellore included in the study. Thorough clinical examination and relevant laboratory investigations performed in all patients Results: Males were commonly affected (72.4%). Fever was the most common presentation (100%), followed by headache (96%) myalgia (94%), abdominal pain (24.46%), and retro-orbital pain (12.45%). Malena was the most common hemorrhagic manifestation. Laboratory findings include varying degree of thrombocytopenia in all patients, leukocytopenia (30.52%), increased hematocrit (>45%) (67.59%) and deranged liver function test (58.33%) Conclusions: Early diagnosis, monitoring, and prompt supportive management can reduce mortality in dengue. Atypical presentations of dengue should be kept in mind, which may cause a delay in the diagnosis. Increased community awareness and vector control measures need to be strengthened during the peri-monsoon period to reduce the burden of dengue cases.